The strangler - Landay, William (New York : Delacorte Press, 2007)
In 1963 Boston, with a mysterious killer, known as the Boston Strangler, stalking the city, the three Daley brothers--Joe, a cop; Michael, a prosecutor; and Ricky, a master thief--track down a killer with ties to their family's own lethal secrets.
Keywords: De Salvo, Albert Henry, -- 1931-1973 -- Fiction; Private investigators -- Fiction; Serial murderers -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction; Historical fiction